2012
DOI: 10.1515/jbnst-2012-0502
|View full text |Cite
|
Sign up to set email alerts
|

The Immigrant-Native Wage Gap in Germany

Abstract: SummaryImmigrant-native wage differentials are observed in many countries, so in Germany. However, the available empirical literature for Germany defined the groups in consideration, immigrants and natives, by citizenship. This limits the explanatory power of the estimates since citizenship distinguishes foreigners and German nationals, but assigns naturalised immigrants (including the large group of ethnic Germans) to the latter group. Providing a more adequate definition based on the concept of origin we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 11 publications
4
37
0
3
Order By: Relevance
“…Результаты эмпирических работ, выполненных на данных зарубежных стран, указывают, что трудовые доходы иммигрантов зачастую ниже, чем у местного населения [Aldashev et al, 2012;Barret, McCarthy, 2007;Borjas, 2015;Demoussis et al, 2010;Lehmer, Ludsteck, 2010]. Исследования дают возможность выявить несколько основных причин разрыва в трудовых доходах между этими двумя группами.…”
Section: обзор литературыunclassified
See 1 more Smart Citation
“…Результаты эмпирических работ, выполненных на данных зарубежных стран, указывают, что трудовые доходы иммигрантов зачастую ниже, чем у местного населения [Aldashev et al, 2012;Barret, McCarthy, 2007;Borjas, 2015;Demoussis et al, 2010;Lehmer, Ludsteck, 2010]. Исследования дают возможность выявить несколько основных причин разрыва в трудовых доходах между этими двумя группами.…”
Section: обзор литературыunclassified
“…Во-первых, иммигранты и местное население могут различаться по уровню и качеству накопленного человеческого капитала, и это будет оказывать влияние на их заработную плату [Aldashev et al, 2012;Becker, 1964;Demoussis et al, 2010;Mincer, 1997]. Индивиды с одинаковым накопленным человеческим капиталом при прочих равных условиях должны иметь одинаковый уровень трудовых доходов [Becker, 1964].…”
Section: обзор литературыunclassified
“…For example, many studies exist on Germany (Lehmer and Ludsteck, 2011). It was found that a significant portion of the wage gap in Germany is caused by the fact that foreign workers with the same characteristics are paid lower wages than locals by 6.7% for men and 15.6% for women (Aldashev et al, 2012). An assessment of the situation in Spain showed that discrimination against lowincome migrants is considerably greater than against high-income foreign workers (Canal-Domínguez and Rodríguez-Gutiérrez, 2007).…”
Section: Literature Surveymentioning
confidence: 99%
“…This blanket statement describes the socalled "wage gap" between natives and migrants that has been observed for many years in many countries. Earnings differentials are found in the United States (U.S.) (Chiswick, 1978;Borjas, 1985;Sanders and Lessem, 2013), Canada (Ferrer et al, 2006), the United Kingdom (U.K.) (Chiswick, 1980;Bell, 1997;Denny et al, 1997;Miranda and Zhu, 2013), and Germany (Pischke, 1992;Dustmann, 1993;Aldashev et al, 2012;Bartolucci, 2014), among others. Non-trivial differences often remain even after factoring out determinants of wages such as educational attainment (see, inter alia, Algan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Using instrumental variables, they show that measurement error leads to a substantial downward bias of the OLS literacy coefficients. Aldashev et al (2012) also rely on SOEP data, and show that increased language skills go hand in hand with increased labor market participation, and that those with a better command of German are more likely to earn higher wages because they are more likely to be employed in white-collar jobs.…”
Section: Introductionmentioning
confidence: 99%